2016
DOI: 10.5152/balkanmedj.2016.141007
|View full text |Cite
|
Sign up to set email alerts
|

Value of Apparent Diffusion Coefficient Values in Differentiating Malignant and Benign Breast Lesions

Abstract: Background: Magnetic resonance imaging (MRI) has become a diagnostic and problem solving method for the breast examinations in addition to conventional breast examination methods. Diffusion-weighted imaging (DWI) adds valuable information to conventional MRI. Aims: Our aim was to show the impact of apparent diffusion coefficient (ADC) values acquired with DWI to differentiate benign and malignant breast lesions. Study Design: Diagnostic accuracy study. Methods: Forty-six women with 58 breast masses (35 maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
2
4
1
Order By: Relevance
“…This fact makes DWI and determination of ADC values a clinically useful additional tool for differentiation of the lesion nature in every day clinical practice. The lowest ADC values were observed in invasive ductal carcinoma (0.68 × 10 −3 mm 2 /s), concordantly with recent studies, where the lowest ADC values were observed in invasive ductal and cribriform carcinoma (0.78 × 10 −3 mm 2 /s), while the highest were observed in micropapillary carcinoma, probably as a result of its typical pathological structure based on the proliferation of tumor cell batches with empty spaces of stroma (15,18). The highest ADC values in malignant lesions in our study were observed in tubulary carcinoma (0.78 × 10 −3 mm 2 /s).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This fact makes DWI and determination of ADC values a clinically useful additional tool for differentiation of the lesion nature in every day clinical practice. The lowest ADC values were observed in invasive ductal carcinoma (0.68 × 10 −3 mm 2 /s), concordantly with recent studies, where the lowest ADC values were observed in invasive ductal and cribriform carcinoma (0.78 × 10 −3 mm 2 /s), while the highest were observed in micropapillary carcinoma, probably as a result of its typical pathological structure based on the proliferation of tumor cell batches with empty spaces of stroma (15,18). The highest ADC values in malignant lesions in our study were observed in tubulary carcinoma (0.78 × 10 −3 mm 2 /s).…”
Section: Discussionsupporting
confidence: 90%
“…According to the results of our study, mean ADC values observed in benign lesions were significantly higher than those observed in malignant lesions, concordantly to the current body of evidence (15)(16)(17). This fact makes DWI and determination of ADC values a clinically useful additional tool for differentiation of the lesion nature in every day clinical practice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the ADC value of the high-risk group was lower than that of the low-risk group in this study, it was found by ROC analysis that Model ADC , which was constructed by applying the ADC value alone, exhibited only limited efficiency in predicting the EC histological grade. The ADC value is a functional imaging indicator commonly employed clinically to reflect the diffusion of water molecules in tissues and it has been widely adopted for the assessment of pathological grades of breast cancer, rectal cancer and other tumors ( 25 , 26 ). Typically, the lower the degree of differentiation of tumor tissues, the larger the nucleus, the greater the number of organelles, the more obvious the nuclear atypia and the larger the nucleo-plasmic ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The single exponential model is useful to distinguish benign from malignant breast lesions, and has been most widely used in clinical practice because of its short scanning time and simple post-processing ( 8 , 10 , 11 ). The ADC model requires two b-values to fit the curve.…”
Section: Introductionmentioning
confidence: 99%